Land Use Dynamics As Livelihoods Risks In Koyefeche-Qilinto Peri-Urban Area, Akaki-Kaliti Sub-City, Addis Ababa - Addis Ayano (My University, 2016)
Land use dynamics is a restless phenomenon all over the world mostly driven by population pressure supported with growing socio-economic interests especially in cities. Addis Ababa city is one of rapidly the rapidly urbanizing cities in Africa. However, there is limitation of empirical evidences on land use dynamics as livelihoods risks of peri-urban settlers. This study has been conducted with the objective of assessing the trends of land use dynamics as livelihoods risks in Koyefeche-Qilinto peri-urban area.In order to achieve the study objective, satellite images were captured and land use dynamics analysis was done using ERDAS EMAGINE 2014 computer software supported with ground survey. On top of this, a questionnaire survey covering a total of 172 sample respondents was conducted to examine the impacts of land use dynamics. The land use dynamics analysis results have shown built-up areas have increased by 1017.85ha (10.178km2) with 47% and 13% decline of forestland and cropland respectively between 1986 and 2016. Even if cropland had a lion share in a horizontal expansion of built-up area as compared to other land use categories, its rate of reduction was very slow due to its illegitimate pressure on forestland.Consequently,46.1ha(51.4%)of forestland was converted to cropland in the study period(1986-2016). Such critical decline of forestland is very inevitable to trigger environmental vulnerability which potentially produces livelihoods risks when it reacts with locally inappropriate implementation strategies & approaches. Multiple linear regression analysis has identified that many of Koyefeche-Qilinto peri-urban settlers are significantly still dependent on agricultural activities after being compensated rather than engaging into non-farm livelihoods activities. On top of this, it was also examined that expropriated peri-urban settlers had not been technically capacitated & supported to utilize their locally available potential livelihoods capitals & compensated payment for adapting urban livelihoods and coping the adverse impact of land use dynamics. Hence, the pre-existing environmental, financial, human, social and physical assets were found to some extent depleted making expropriated peri-urban settlers vulnerable to adverse effect of land use dynamics contexts. Hence, pre-expropriation & displacement defensive measures associated with DRR and post-expropriation & displacement adaptation measures related to strengthening institutional capacity, community operational ability and promoting environment friendly high market value agricultural production are recommended in the study to mitigate the occurrence of livelihoods risks due land use dynamics in the peri-urban settlements.